Physicians’ Perspectives, Well-being, and Fulfilment in Telemedicine: A Cross-Sectional Study - Cristina Sicorschi Gutu; Krisztina Schmitz-Grosz; Carsten Sommer-Meyer; Günter Niklewski (Telemedicine Reports)
Background: Telemedicine, a safe way of medical care appreciated by patients, has proven to have different benefits for our health care systems. Studies on patient experiences and outcomes in telemedicine are thriving. However, few studies have explored the possible associations between telemedicine and physician work–life balance or mental health. Methods: A cross-sectional survey for physicians who practiced in Switzerland was conducted. Physicians who participated answered validated questions about work–life balance, professional satisfaction, emotional exhaustion, and depression. There were three groups a control group with physicians who did not practice telemedicine (n = 30), an experimental group with physicians who practiced telemedicine (n = 32), and a group with physicians who left telemedicine (n = 31). The 42-question survey was open between June and August of 2023. Participation was optional, anonymous, and voluntary. Results: In total, 93 participants completed the questionnaire. In terms of work–life balance, the best results were observed in the telemedicine group (4.63 vs. 4.35 in the control group). A high level of exhaustion was observed in 26.7% of the control group compared with 12.5% of the telemedicine group. Low professional fulfillment was present in 62.5% of participants in the telemedicine group vs. 46.7% of participants in the control group. Among the telemedicine physicians, 21.9% of participants were suspected of having depression. Discussion: Practicing telemedicine as a profession may have a positive impact on physicians’ work–life balance and burnout. Further research is necessary to explore the long-term effects of telemedicine on physicians’ mental health.